Naked hitchhikers: the unknown photography of William A. Rhoads. Issue 1 (2nd January 2017) - Johnson, Dominic
ABSTRACT: William A. Rhoads was an avid photographer of male nudes, mostly sourced from hitchhikers he picked up in California in the 1970s. His efforts were prolific and sustained – and secret – and likely made and retained for private enjoyment. The photographs were never shown in public in Rhoads' lifetime. I approach his project, firstly, from the perspective of its historical and cultural contexts of emergence and development; and secondly in terms of the taxonomic challenges his photographs pose, in relation to established histories of art and pornography, which were being called strikingly into question in the 1970s. Both approaches allow Rhoads to be understood beyond the traditional aesthetic distinction between art and pornography – or more precisely, between a personal, erotic practice and a formal artistic one.